2023
DOI: 10.1186/s13005-023-00354-5
|View full text |Cite
|
Sign up to set email alerts
|

Differences in characteristics and infection severity between odontogenic and other bacterial oro-naso-pharyngeal infections

Abstract: Background Different bacterial infections of the oro-naso-pharyngeal (ONP) region may progress and require hospital care. The present study clarified differences in infection characteristics between hospitalized patients with odontogenic infections (OIs) and other bacterial ONP infections. The specific aim was to evaluate clinical infection variables and infection severity according to infection aetiology, particularly regarding features of OIs compared with other ONPs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Considering the staying lenght of hospitalization, the highest average number of days is found in patients with diabetes mellitus (3.6% of the 146 hospitalized patients). This result is important, as it is known that compromised immune systems can lead to the opportunistic progression of apparently minor infections, increasing the chances of superficial oral abscesses into the deep neck infections 27,28 . It is in accordance with the found data of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the staying lenght of hospitalization, the highest average number of days is found in patients with diabetes mellitus (3.6% of the 146 hospitalized patients). This result is important, as it is known that compromised immune systems can lead to the opportunistic progression of apparently minor infections, increasing the chances of superficial oral abscesses into the deep neck infections 27,28 . It is in accordance with the found data of our study.…”
Section: Discussionmentioning
confidence: 99%
“…20 Multiple studies have indicated that male patients face a higher risk of hospitalization following surgeries and a greater likelihood of requiring intensive care unit (ICU) treatment. 14,21 However, there were also studies showing little correlation between gender and OMSI severity in terms of length and cost of hospitalization, severe complications and reoperation risk. 3,10,17 The nal regression model of our study retained gender as a risk factor associated with the outcome.…”
Section: Discussionmentioning
confidence: 99%